Legal, Fiscal and Pro-Family Aspects of the Deduction for Raising Children - Małecka-Ziembińska, Edyta (Studia Oeconomica Posnaniensia, 2016)
In the face of unfavorable demographic indicators the central government has undertaken activities aimed at improving the current situation. The pro-family politics were implemented by the introduction of the allowance for parents raising children in 2007. The requirements and rules regarding this allowance have been altered multiple times since its introduction. This paper is focused on the eligibility criteria during recent years. It discusses the related costs and fiscal consequences for local governments. Further it tries to evaluate the impact of the allowance on society and its other application effects.